Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1017/s0033291718000557
|View full text |Cite
|
Sign up to set email alerts
|

The risk of developing major depression among individuals with subthreshold depression: a systematic review and meta-analysis of longitudinal cohort studies

Abstract: The results of this study support the scaling up of effective indicated prevention interventions for people with subthreshold depression, regardless of age group or setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 41 publications
1
85
0
Order By: Relevance
“…Hence, our findings cannot be directly generalized to populations with severe and clinically significant depressive symptomatology. Nevertheless, a recent review highlighted that more research should be directed at understanding subclinical depression, since it strongly predicts later clinical depression and could provide new tools for tailoring early and preventive interventions (Lee et al, 2018). This was the Dispositional compassion and depressive symptoms primary aim of the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, our findings cannot be directly generalized to populations with severe and clinically significant depressive symptomatology. Nevertheless, a recent review highlighted that more research should be directed at understanding subclinical depression, since it strongly predicts later clinical depression and could provide new tools for tailoring early and preventive interventions (Lee et al, 2018). This was the Dispositional compassion and depressive symptoms primary aim of the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Two recent studies have reported increased symptoms of anxiety, symptoms of eating disorder and other psychiatric symptoms among psychiatric patients during the COVID-19 pandemic [4]. This may be signi cant also for individuals with minor mental health problems because they are at risk for developing more severe problems [22][23][24].…”
Section: Mental Health Problemsmentioning
confidence: 99%
“…Within the preventive spectrum, prioritized attention should be given to preventive interventions that focus on treating subclinical depressive symptoms to prevent progression to full-blown depressive episodes (i.e., indicated prevention). These interventions are especially cost-effective because they focus on populations with a higher incidence of the disorder because subclinical depressive symptomatology is a factor that doubles the probability of developing major depression [13]. In addition, such preventive interventions are clinically useful in and of themselves because subclinical symptoms are one of the main risk factors for a depressive episode [14], produce clinically significant discomfort and functional impairment [15], have economic costs comparable to those of major depression [16], and increase the risk of mortality [17,18].…”
Section: Introductionmentioning
confidence: 99%